2016
DOI: 10.1016/j.jcp.2015.11.060
|View full text |Cite
|
Sign up to set email alerts
|

An FC-based spectral solver for elastodynamic problems in general three-dimensional domains

Abstract: This paper presents a spectral numerical algorithm for the solution of elastodynamics problems in general three-dimensional domains. Based on a recently introduced "Fourier continuation" (FC) methodology for accurate Fourier expansion of non-periodic functions, the proposed approach possesses a number of appealing properties: it yields results that are essentially free of dispersion errors, it entails mild CFL constraints, it runs at a cost that scales linearly with the discretization sizes, and it lends itsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(102 citation statements)
references
References 25 publications
3
99
0
Order By: Relevance
“…Significant progress occurred over the life of this contract in the area of FC (Fourier Continuation) methods for Partial Differential Equations in the time-domain [1][2][3][4][5][6][7]. Our efforts in these areas have resulted in explicit and implicit solvers for high-and low-frequency problems, for linear and nonlinear equations, and including media such as fluids, solids and vacuum-and combinations thereof.…”
Section: Time-domain Fourier-continuation Solversmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant progress occurred over the life of this contract in the area of FC (Fourier Continuation) methods for Partial Differential Equations in the time-domain [1][2][3][4][5][6][7]. Our efforts in these areas have resulted in explicit and implicit solvers for high-and low-frequency problems, for linear and nonlinear equations, and including media such as fluids, solids and vacuum-and combinations thereof.…”
Section: Time-domain Fourier-continuation Solversmentioning
confidence: 99%
“…In the contribution [2], in turn, methods for FC solution of problems containing variable coefficients were introduced; in particular it was found that certain numerical boundary layers need to be adequately represented in order to ensure accurate solution. Reference [3] introduced an approach that allows for treatment of traction boundary conditions in wave propagation problems in solids [3,4] (Navier's elastic wave equation) 1 . The thesis [5] uses the Fourier Continuation method in multiple ways: to solve equations, to propagate to distant regions without meshing, etc.…”
Section: Time-domain Fourier-continuation Solversmentioning
confidence: 99%
“…[11]). More recently, the FC methodology was combined with an overset grid approach for the solution of the compressible Navier-Stokes equations in two dimensions [12] and the elasticity equations in three dimensions [13]. A key development in those contributions is the extension of the FC method [14] to overlapping "sub-patch" block-decompositions of larger meshes.…”
Section: Introductionmentioning
confidence: 99%
“…A key development in those contributions is the extension of the FC method [14] to overlapping "sub-patch" block-decompositions of larger meshes. Although the contributions [12,13] have successfully used the overset method in the context of explicit solvers, the goal of extending the framework to implicit and multi-domain implicit-explicit solvers had not been realized until now.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation